(3QSGdI aj eYfi bhdg JYGdi (B( (3hdh CfeG aj GdCQV ef TLQI CbdGe hGdHMQ jeOg (B) (3hbhdg JYGdi (B( (3bd dh cGf GdHMQ eOGOkG dcdeGJ QHj (B)s - (3eMeO GdSYjO Hf eMjj GdOjf GdMSfj GdLRGFQj,J (B1278 (3g` s ((3YHO GdbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg hHYO aEfc SCdJ Yf eYfi bhdg JYGdi (B( (3hdh CfeG ai GdCQV ef TLQI CbdGe hGdHMQ jeOg ef HYOg SHYI CHMQ eG faOJ cdeGJ Gddg (B) s
(3BNQgG (B:s
(3aGdLhGH Cf cd eG CfRdg Gddg YdjfG aEfeG CfRdg daGFOg ajg hefaYg dfG aBjg jhSa ebJOi HgG eYehd YdjgG GfJgi hcJHJ ebjOkG dPdc eMeO GdSYj(B\(3O Hf eMi GdOjf HChGSW LeGOi GdChdi YGe (B1278 (3g` s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs